Couples' experiences with sexuality after spinal cord injury. Issue 4 (13th February 2023) - Osborne, Jake B.; Rocchi, Meredith A.; McBride, Christopher B.; McKay, Rhyann; Gainforth, Heather L.; Upper, Randy; Sweet, Shane N.
Abstract: Purpose: To explore sexuality after spinal cord injury (SCI) from the perspectives of individuals with SCI and their romantic partners. Methods: A sample of 8 Canadian adults with SCI (6 men, 2 women) and their partners participated in this study ( N = 16). Semi-structured dyadic and individual interviews were conducted, discussions surrounding sexuality and intimacy were extracted, and a qualitative description of the interview data was performed using thematic analysis. Results: Three major themes were identified: the changing definition of sex; emotions; and practical support. Couples' conversations around the changing definition of sex after SCI addressed the taboo topic of sexuality and the importance of communication between couples, peers, and healthcare providers. Emotions included fears of losing intimacy, embarrassment in managing bladder and bowel interference, and acceptance in balancing being a romantic partner and a caregiver. Finally, couples reported challenges accessing practical support including medical interventions and sexual health nurses, but saw value in peer mentorship programs. Conclusion: Couples explored a changing definition of sex following SCI that was complicated by the taboo nature of discussing sexuality, experienced a range of emotions throughout the recovery process, and had difficulties navigating the healthcare system for appropriate support. IMPLICATIONS FOR REHABILITATION: Healthcare professionals should promote discussion and provide support for sexuality following SCI, but during initial rehabilitation may be too early. Healthcare providers should prepare people with SCI and their partners for the inevitable trial-and-error process involved in sexual rehabilitation. Rehabilitation professionals could direct couples to SCI peer mentorship programs to help normalize the experiences and emotions of sexual rehabilitation.